PENGARUH MONITORING TERHADAP KINERJA PEGAWAI PADA PERUSAHAAN UMUM DAERAH (PERUMDA) AIR MINUM KOTA MAKASSAR - Herfian, Aqshal Muhammad Ilham; Anwar, Anwar; Burhanuddin, Burhanuddin (Bussman Journal : Indonesian Journal of Business and Management, 2024)
This study aims to determine the effect of monitoring on employee performance at the Regional Public Company Makassar City drinking water. This type of research is quantitative associative in nature. The population is 89 employees at the Makassar City Drinking Water Office. The sampling technique used was saturated sample so that the total sample was 89 respondents. The data collection technique was carried out by distributing questionnaires to employees. The data analysis technique uses simple regression with the help of SPSS version 27 software. The results of this study indicate that monitoring has a positive and significant effect on the performance of employees of the Regional Public Company (Perumda) Makassar City drinking water